Parallel Teaching and Evaluation of Employability and Foreign Language Competencies in Technical Language Training - Zita Hajdu; Ildikó Tar; Tímea Lázár; János Farkas; Mária Czellér (Humán Innovációs Szemle)
An increasingly important expectation of today’s labour market is the group of employability skills. That is the reason why the Institute of Business Communication and Professional Language Studies at Debrecen University found it essential to introduce the development of these highly demanded competences in the curriculum of the technical language courses. The paper describes how workplace skills and foreign language competencies can be compiled in one curriculum with particular emphasis on the application of IT skills in foreign language courses. Since a major task of universities is to prepare students for the tasks of assessment centres and other stages of the selection process, the testing of non-cognitive skills should also be integrated into the teaching material. The expected results of the program include: achieving a higher level of professional language and soft skills, increased student confidence in workplace situations and improved general communication skills.